Empowering School Communities Through Business Management And Basic Financial Literacy Training: A Case Of SD Muhammadiyah 2 Sukmajaya Depok - Ade Ghofir; Ramdany Ramdany; Viniyati Maftuchach; Maria Suryaningsih; Alvandi Dwi Hardiyanto (Yayasan Darussalam Bengkulu, 2026)
This study aims to enhance the financial management capacity of educators and administrative staff through a Community Service Program (PKM) focusing on business management and simple financial recording training at SD Muhammadiyah 2 Sukmajaya, Depok. The program was designed in response to the limited understanding of management principles and the unsystematic financial recording practices identified during the initial needs assessment. A participatory and application-oriented approach was employed, including interactive lectures, discussions, simulations, and hands-on practice. A total of 15 participants were involved in the training, and evaluation was conducted using pre-test and post-test assessments, practical exercises, and participant feedback. The results indicate a significant improvement in participants’ knowledge, as reflected in the increase in the average score from 50 (pre-test) to 85 (post-test). In addition, participants demonstrated improved skills in preparing simple financial records, including cash books and basic financial statements. The findings suggest that structured training and mentoring effectively enhance financial literacy and administrative competencies. Furthermore, the program contributes to promoting transparency, accountability, and efficiency in school financial governance, while fostering sustainable financial management practices within educational institutions.